2021
DOI: 10.5194/piahs-384-85-2021
|View full text |Cite
|
Sign up to set email alerts
|

Pollution des eaux à usages domestiques par les éléments traces métalliques des activités anthropiques : cas du sous bassin versant du fleuve Sassandra en amont du barrage de Buyo, Côte d'Ivoire

Abstract: Abstract. Pour résoudre les problèmes d'approvisionnement en eau potable des centres urbains, le gouvernement ivoirien a décidé d'utiliser les ressources pérennes telles que le fleuve Sassandra. Ainsi, le sous bassin du fleuve Sassandra en amont du barrage de Buyo est pressenti pour alimenter les villes de la région du Haut Sassandra et du département de Duekoué. Cependant, les intrants agricoles, les activités d'orpaillage et les déchets ménagers entrainent une forte contamination des eaux de ce fleuve en élé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…where E r i = individual ecological risk index; Cfi = contamination coefficient for metal i; Cei = concentration of metal i in the sample; Cri = concentration of metal i in unpolluted sediments/ reference concentration; Tfi = toxicity weight or weighting factor for metal i. The pre-industrial concentrations of lead and cadmium (17.0 and 0.102 mg•kg -1 ) were used as the concentrations of unpolluted sediments (Konan et al, 2021). The respective weights assigned to the metals used in the calculations were: cadmium = 30 and lead = 5.…”
Section: Heavy Metal Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…where E r i = individual ecological risk index; Cfi = contamination coefficient for metal i; Cei = concentration of metal i in the sample; Cri = concentration of metal i in unpolluted sediments/ reference concentration; Tfi = toxicity weight or weighting factor for metal i. The pre-industrial concentrations of lead and cadmium (17.0 and 0.102 mg•kg -1 ) were used as the concentrations of unpolluted sediments (Konan et al, 2021). The respective weights assigned to the metals used in the calculations were: cadmium = 30 and lead = 5.…”
Section: Heavy Metal Contaminationmentioning
confidence: 99%
“…The assessment of sediment pollution status is based on the calculation of indices rather than a comparison of metal concentrations against reference values (Adje et al, 2021;Konan et al, 2021). The potential Ecological Risk Index (ERI) was used for this purpose.…”
Section: Characterization Of Stations: Relationship Between Physicoch...mentioning
confidence: 99%
“…The presence of toxic heavy metals in water, whether naturally occurring or due to human activity, poses a public health issue when concentrations surpass established safety thresholds [16] [17]. Nonetheless, the effects of heavy metal and pesticide pollution resulting from accidental or chronic buildup of these substances in the environment are not yet adequately researched [18].…”
Section: Introductionmentioning
confidence: 99%
“…Localities housing illegal gold mining sites such as Kong 2 (Yakassé Attobrou department), Degbézéré (Bouaflé department) and Aboisso are contaminated by heavy metals. Most of the rivers of Côte d'Ivoire are polluted due to gold panning, these are the Cavally, the Sassandra, the Bandama and the N'zi [4,5]. Numerous studies have found metal levels above the limit values set by the WHO in the surface waters of several localities hosting illegal gold panning sites in Côte d'Ivoire [6,7].…”
Section: Introductionmentioning
confidence: 99%